Evaluasi Kinerja Saluran pada Sistem Drainase Kawasan UPN “Veteran” Jawa Timur - Muchammad Ali Fikri; Syadzadhiya Qothrunada Zakiyayasin Nisa’; R Mohammad Alghaf Dienullah (Fakultas Teknik Universitas Cenderawasih, 2026)
The drainage system is critical infrastructure for managing stormwater runoff in densely built urban areas, including higher education institutions. This study aims to evaluate the capacity performance of the existing drainage channels in the UPN